1990
DOI: 10.1001/archotol.1990.01870060050008
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of a Vascular Smooth-Muscle Actin in Salivary Gland Tumors

Abstract: In an attempt to determine if both pleomorphic adenomas and adenoid cystic carcinomas are derived from myoepithelial cells, 23 pleomorphic adenomas, 22 adenoid cystic carcinomas, and 17 normal salivary glands were examined immunohistochemically by using monoclonal antibodies directed against actin (HUC1-1, 1A4), keratin (AE-1, 34 beta E 12), and vimentin (V9). In normal salivary glands, the myoepithelial cells demonstrated a positive reaction to the monoclonal antibodies against actin and only rarely reacted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…It has been often difficult to identify vimentin immunostaining in MECs [18,24,33,37], probably due to its restricted distribution in the cytoplasm [19,23]. Despite this difficulty, the present and the previous [6,24,25] studies observed distinct vimentin staining in MECs. In this context, some authors have recommended this protein as a MEC marker [2,3,33].…”
Section: Discussionmentioning
confidence: 60%
“…It has been often difficult to identify vimentin immunostaining in MECs [18,24,33,37], probably due to its restricted distribution in the cytoplasm [19,23]. Despite this difficulty, the present and the previous [6,24,25] studies observed distinct vimentin staining in MECs. In this context, some authors have recommended this protein as a MEC marker [2,3,33].…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, coexpression of keratin 14 and a-smooth muscle actin (aSMA) has been the most widely used marker for identification of MECs [6-8, 14, 21, 22, 29, 31, 48, 50, 55]. Tumor cells with keratin 14 are more abundant than are those with aSMA in certain tumors, such as pleomorphic adenoma and adenoid cystic carcinoma [6,8,22,31,34,48,55,56,60]. By definition, the neoplastic cells expressing keratin 14 alone (without aSMA) are not necessarily derived from MECs.…”
Section: Introductionmentioning
confidence: 99%
“…Later, alphasmooth muscle actin (ct-SMA) was demonstrated in normal MEC of a salivary gland, and turned into its standard marker, even in neoplasms. Nevertheless, later studies showed that neoplastic MEC may not express oc-SMA [4][5][6][7][8][9]. Vimentin has also been used as a neoplastic MEC marker [10][11][12][13][14][15], and was indicated as an early marker of myoepithelial differentiation, being present in all morphologic types that the MEC may assume [9,16,17].…”
mentioning
confidence: 99%